Penguatan Pertemanan Positif melalui Psikoedukasi untuk Meningkatkan Kesadaran Anti-Bullying pada Siswa SMPN 12 Surabaya - Arifah Devinta Arfianty; Yessi Octavia; Fadiah Ulil Abshar; Evelyna Shafa Maretta; Illene Nathania Evelyna Zeva; Farah Dila Dewi; Nadiah Qonita; Inka Sukma Melati; Niken Titi Pratitis (Universitas Pangeran Diponegoro Nganjuk, 2026)
Negative peer relationships and bullying behavior among adolescents constitute significant social issues that affect students’ psychological well-being and the overall school climate. This psychoeducational intervention aimed to enhance students’ understanding and awareness of positive peer relationships as a preventive strategy against bullying at SMPN 12 Surabaya. The program employed a participatory psychoeducation approach, incorporating interactive lectures, educational videos, group games, and sharing sessions. Program effectiveness was evaluated using a pre-test and post-test design to measure changes in participants’ understanding. The findings indicate a substantial increase in students’ comprehension of positive peer relationships, rising from 30.9% in the pre-test to 78.8% in the post-test. Beyond cognitive improvement, the intervention also fostered more supportive and empathetic social interactions among students. These results suggest that participatory psychoeducation can serve as an effective strategy for promoting anti-bullying awareness and strengthening positive peer dynamics in junior high school settings.